The Influence of Knowledge, Trust, Perceived Usefulness, Security, and Service Features on Customers’ Adoption of Internet Banking - Yolanda; Ronald Suryaputra; Widi Dewi Ruspitasari (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of knowledge, trust, perceived usefulness, security, and service features on customers’ decisions to use Internet Banking. The research employed a quantitative, associative research design to examine causal relationships among variables. Data were collected through questionnaires distributed to 120 bank customers who had previously used Internet Banking services. The data were analyzed using multiple linear regression supported by statistical software to examine both partial and simultaneous effects of the independent variables on customers’ decisions. The results show that knowledge, trust, perceived usefulness, security, and service features each have a positive and significant effect on customers’ decisions to use Internet Banking. Among these variables, perceived usefulness was found to be the most dominant factor influencing adoption decisions. The simultaneous test also indicates that all independent variables collectively have a significant effect on customers’ decisions to adopt Internet Banking services. These findings imply that improving customers’ understanding of digital banking, strengthening system security, building customer trust, and enhancing service features are essential strategies for increasing the adoption of Internet Banking services.